Answer:
Please check the explanation.
Explanation:
The slope-intercept form of the line equation
y = mx+b
where
Part a)
Given the equation
![9x-3y-9=0](https://img.qammunity.org/2022/formulas/mathematics/college/d04q72xabu9n0cfpb3s788ut6u2n499b89.png)
Writing the equation in the slope-intercept form of the line equation
![9x-3y-9=0](https://img.qammunity.org/2022/formulas/mathematics/college/d04q72xabu9n0cfpb3s788ut6u2n499b89.png)
adding 3y to both sides
![9x-3y-9+3y=0+3y](https://img.qammunity.org/2022/formulas/mathematics/college/zlxqo50tgtqzn92jdohqg8p93i76npc6s2.png)
![9x-9 = 3y](https://img.qammunity.org/2022/formulas/mathematics/college/18tymcxdo8mqpqsjg2t6hpt3t0dcmpk0r9.png)
flip the equation
![3y = 9x-9](https://img.qammunity.org/2022/formulas/mathematics/college/gwwfy8civ5b7fr8r12knca8sjcdv7763h3.png)
divide both sides by 3
![y=3x-3](https://img.qammunity.org/2022/formulas/mathematics/college/1i77fdw6vmkjyw6lvkd11lsra9sq3uv0fn.png)
Thus, the equation in the slope-intercept form is:
![y=3x-3](https://img.qammunity.org/2022/formulas/mathematics/college/1i77fdw6vmkjyw6lvkd11lsra9sq3uv0fn.png)
Part b)
As the equation in the slope-intercept form is
![y=3x-3](https://img.qammunity.org/2022/formulas/mathematics/college/1i77fdw6vmkjyw6lvkd11lsra9sq3uv0fn.png)
comparing with the slope-intercept form
Part c)
Given the equation
![y=3x-3](https://img.qammunity.org/2022/formulas/mathematics/college/1i77fdw6vmkjyw6lvkd11lsra9sq3uv0fn.png)
The graph is attached below.
From the given graph, is clear that:
at x = 0, the value of y = -3
Thus, the y-intercept of the equation is b = -3
Please check the attached graph.